2008
DOI: 10.1088/1468-6996/9/4/044202
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional pairing in doped band insulators on a honeycomb lattice: the role of the disconnected Fermi surface and a possible application to superconducting β-MNCl (M=Hf, Zr)

Abstract: We investigate the possibility of realizing unconventional superconductivity in doped band insulators on the square and honeycomb lattices. The latter lattice is found to be a good candidate due to the disconnectivity of the Fermi surface. We propose applying the theory to the superconductivity in doped layered nitride β-MNCl (M = Hf, Zr). Finally, we compare two groups of superconductors with disconnected Fermi surface, β-MNCl and the iron pnictides, which have high critical temperature T c , despite some fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Such low dimensionality of the crystal could cause inhomogeneous electronic states because of the possible electronic fluctuations. The theoretical study of the lattice-dependent superconductivities was also reported by Kuroki et al 28 It shows that the superconductivity of the honeycomb lattice is robust toward the changing of the leveloffset energy between the M and N networks of MN lattice, while that of the square lattice has the strong dependence on the level-offset energy. If we assume that these offset energies vary spatially, it is consistent with our experimental results of the more homogeneous superconductivity occurring in honeycomb lattice of HfNCl y .…”
Section: Methodsmentioning
confidence: 53%
“…Such low dimensionality of the crystal could cause inhomogeneous electronic states because of the possible electronic fluctuations. The theoretical study of the lattice-dependent superconductivities was also reported by Kuroki et al 28 It shows that the superconductivity of the honeycomb lattice is robust toward the changing of the leveloffset energy between the M and N networks of MN lattice, while that of the square lattice has the strong dependence on the level-offset energy. If we assume that these offset energies vary spatially, it is consistent with our experimental results of the more homogeneous superconductivity occurring in honeycomb lattice of HfNCl y .…”
Section: Methodsmentioning
confidence: 53%
“…19 Furthermore, muon spinrelaxation measurements 20 and specific-heat measurements have revealed that the superconducting order parameter is highly anisotropic, as it has been also suggested theoretically. 21 These experimental and theoretical observations would suggest a possible pairing mediated by magnetic fluctuations, despite the nonmagnetic band insulator nature of the present compounds ZrNCl and HfNCl.…”
Section: Introductionmentioning
confidence: 63%
“…A recent study of the doping variation in the magnetic susceptibility along with theoretical calculations 19,35 have suggested an evolution of magnetic fluctuations from reduced carrier density and its contribution to the pairing interaction in the parent material. According to the theory, in Li x ZrNCl which has two degenerated nearly cylindrical Fermi surfaces centered at K and KЈ points in the hexagonal Brillouin zone, the pairing can be mediated by a spin fluctuation, 21 and the enhancement and the subsequent constant behavior of T c with improvement of two dimensionality have been demonstrated by the calculation. 35 Within this scheme, as the interlayer spacing d is increased, the Fermi surface warping along the k z direction must be reduced due to enhanced two dimensionality and that would result in an increase in nesting of the Fermi surface.…”
Section: Discussionmentioning
confidence: 99%
“…These behaviors cannot be understood in the framework of the Bardeen, Cooper, and Schrieffer (BCS) mechanism. The electron-doped β-ZrNCl and β-HfNCl are considered to be unconventional superconductors; these have attracted much attention from theoretical as well as experimental physicists. ,,, …”
Section: Introductionmentioning
confidence: 99%